Розробка системи автоматизованого запису на послуги за допомогою telegram-бота - Коврига, І. В. (ХНУРЕ, 2025)
This paper is devoted to the development of a Telegram bot for automating the service booking process. The proposed bot aims to improve service accessibility, reduce administrative workload, and enhance user experience. The research covers the selection of technologies, bot architecture, and implementation details. The effectiveness of the developed system is evaluated based on performance indicators and user feedback. The findings demonstrate that the bot significantly streamlines the booking process, improves service efficiency, and serves as a valuable tool for both users and administrators.
Keywords: автоматизований запис; telegram бот